2017
DOI: 10.1177/0363546517704178
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Time to Recurrent Ipsilateral and Contralateral Patellar Dislocations

Abstract: At 20 years after a first-time lateral patellar dislocation, the cumulative incidence of recurrent ipsilateral patellar dislocations was 36.0%, compared with 5.4% for contralateral dislocations. Trochlear dysplasia, elevated TT-TG distance, patella alta, age <18 years at the time of the first dislocation, and female sex were associated with ipsilateral recurrence. Trochlear dysplasia, elevated TT-TG distance, patella alta, and age <18 years at the time of the first dislocation were predictive of a statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(183 citation statements)
references
References 28 publications
8
168
1
1
Order By: Relevance
“…Specifically, the TT-TG distance, trochlear sulcus angle and lateral trochlear inclination angle showed particularly strong correlation coefficients, while the patella height (CDI) strongly correlated with the dynamic patellar tilt. These observations support the findings of previous studies, which have identified the trochlear shape and TT-TG as particularly strong predictive parameters for patellofemoral instability 42,43 . In this context, dynamic MRI could provide important valuable additional information to evaluate the influence of present risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, the TT-TG distance, trochlear sulcus angle and lateral trochlear inclination angle showed particularly strong correlation coefficients, while the patella height (CDI) strongly correlated with the dynamic patellar tilt. These observations support the findings of previous studies, which have identified the trochlear shape and TT-TG as particularly strong predictive parameters for patellofemoral instability 42,43 . In this context, dynamic MRI could provide important valuable additional information to evaluate the influence of present risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…In the pediatric population, non-operative management of recurrent PFI has a high recurrence rate that can affect activities of daily life [5]. However, operative management is not without complications.…”
Section: Complications Of Stabilizationmentioning
confidence: 99%
“…Reasons for this adolescent predominance may include rapid skeletal growth with changes in lower extremity mechanics and alignment, ligamentous laxity, early sports specialization, and increase in high-risk activity level [4]. While first-time dislocation may be successfully managed non-operatively with proper rehabilitation, bracing, and activity modification, up to 36% of patients have ipsilateral recurrent PFI [5]. While epidemiologic studies have demonstrated a relatively consistent incidence of PFI over time [1], studies have found an increasing incidence of surgery to treat PFI reflecting the trends towards earlier operative management of this condition [6].…”
Section: Introductionmentioning
confidence: 99%
“…18,[93][94][95][96] In some series, acute patellar dislocations have been up to 33% more frequent in female versus male adolescents, and moreover females have approximately double the risk of recurrent dislocations. 8,97,98 Some have attributed this discrepancy to females tending to have higher grades of underlying anatomical abnormalities relative to males. 97 Recurrent subluxations and dislocations can occur with relatively minor trauma or sports activities.…”
Section: Patellar Instabilitymentioning
confidence: 99%